Type 2 diabetes and dementia in the Health and Retirement Study: A Mendelian randomization approach: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Ware, Erin B; Bustamante, Ana Cristina Morataya; Fu, Mingzhou; Bakulski, Kelly M
Abstract: Background: Type 2 diabetes mellitus (T2DM) and dementia are leading causes of mortality and disability in the US. T2DM has been associated with dementia; however, causality has not been established. The aim of this study is to test for an association between T2DM and dementia status using a Mendelian randomization approach. Method: Participants from the 2010 wave of the longitudinal Health and Retirement Study, a nationally representative survey of US adults over the age of 50, and who were of European or African genetic ancestry were included in the study (n=10, 571). History of T2DM was self‐reported. Cognitive status was defined from clinically validated cognitive assessments as dementia, cognitively impaired non‐dementia, or normal cognition. Cumulative genetic risk for T2DM and dementia was determined using polygenic risk scores. Multivariable logistic regression was used to test the association between cumulative genetic risk for T2DM and cognitive status adjusting for age, sex, education, APOE ‐ε4 carrier status, and genetic principal components. The inverse variance method was used to test inferred causality using Mendelian randomization. Result: Among included participants, 20.75% had T2DM and 21.8% had dementia or cognitive impairment. Among European ancestry participants, T2DM was associated with 1.28 times odds of cognitive impairment non‐dementia (95% confidence interval: 1.09‐1.50) relative to normal cognition. A one standard deviation increase in cumulative genetic risk for T2DM was associated with 1.43 times higher odds of T2DM (95% confidence interval: 1.33‐1.54). Cumulative genetic risk for T2DM was not associated with dementia status or cognitive‐impairment non‐dementia in either ancestry ( P >0.05); lack of association here is an important assumption of Mendelian randomization. Using Mendelian randomization, we did not observe evidence for an inferred causal association between T2DM and cognitive impairment (odds ratio: 1.08; 95% confidence interval: 0.86‐1.37). Conclusion: Consistent with prior research, T2DM was associated with cognitive status. In the current study; however, evidence for inferred causality was not observed. Prevention of T2DM and cognitive decline are critical for public health.